International Cooperation on WMD Nonproliferation - Knopf, Jeffrey W. (Book collections on Project MUSE., 2016)
International efforts to prevent the spread of weapons of mass destruction (WMD)-including nuclear, biological, and chemical weapons-rest upon foundations provided by global treaties such as the Nuclear Non-Proliferation Treaty (NPT) and the Chemical Weapons Convention (CWC). Over time, however, states have created a number of other mechanisms for organizing international cooperation to promote nonproliferation. Examples range from regional efforts to various worldwide export-control regimes and nuclear security summit meetings initiated by U.S. president Barack Obama. Many of these additional.